SIRT3 inhibits autophagy-dependent ferroptosis of HUVECs in the progression of pregnancy-induced hypertension by activating the PI3K/Akt/mTOR axis - Li, Yanchuan; Liu, Yanfeng; Shi, Ziyun; He, Meiqing (Frontiers in Molecular Neuroscience, 2025)
IntroductionPregnancy-induced hypertension (PIH) is a major contributor to increased maternal and neonatal morbidity and mortality worldwide. Accumulating evidence suggests that vascular endothelial cell injury is a key pathological feature in the development of PIH; however, the underlying molecular mechanisms remain incompletely understood. This study aimed to investigate the role of sirtuin 3 (SIRT3) in regulating autophagy and ferroptosis in endothelial cells under hypoxic conditions, and its potential impact on PIH pathogenesis.MethodsHuman umbilical vein endothelial cells (HUVECs) were subjected to hypoxia/reoxygenation (H/R) to mimic ischemic-reperfusion injury associated with PIH. Autophagy levels were assessed by measuring the ratio of microtubule-associated protein light chain 3 (LC3)-II/LC3-I and sequestosome 1/p62 expression. Ferroptosis markers, including intracellular iron, reactive oxygen species (ROS), malondialdehyde (MDA), glutathione (GSH), and glutathione peroxidase 4 (GPX4), were evaluated. SIRT3 was overexpressed using pcDNA-SIRT3, and autophagy was modulated with rapamycin or SIRT3 overexpression. The involvement of the PI3K/Akt/mTOR pathway was examined by Western blotting. In vivo validation was performed using a rat model of PIH with SIRT3 overexpression, followed by analysis of placental tissue for relevant protein expression and signaling pathway activation.ResultsH/R treatment induced autophagy in HUVECs, as evidenced by increased LC3-II/LC3-I ratio and decreased p62 levels. It also triggered ferroptosis, characterized by elevated iron, ROS, and MDA levels, along with reduced GSH and GPX4 expression. Overexpression of SIRT3 suppressed both H/R-induced autophagy and ferroptosis, and these protective effects were reversed by the autophagy inducer rapamycin or the ferroptosis inducer erastin. Mechanistically, SIRT3 activated the PI3K/Akt/mTOR signaling pathway, and inhibition of this pathway attenuated the suppressive effects of SIRT3 on autophagy and ferroptosis. In PIH rats, SIRT3 overexpression increased the levels of SIRT3 and GPX4, enhanced phosphorylation of PI3K, Akt, and mTOR, and reduced the LC3-II/LC3-I ratio in placental tissues compared to control PIH rats.DiscussionThese findings demonstrate that SIRT3 protects against hypoxia-induced endothelial cell injury by inhibiting autophagy-dependent ferroptosis through activation of the PI3K/Akt/mTOR signaling pathway. The in vivo results further support a protective role of SIRT3 in alleviating PIH. This study reveals a novel SIRT3-mediated regulatory mechanism in PIH pathophysiology, suggesting that targeting SIRT3 and its downstream signaling may represent a potential therapeutic strategy for the management of PIH.